The Two-Stroke Poppet Valve Engine. Part 1: Intake and Exhaust Ports Flow Experimental Assessments - Muhammad Kamili, Zahidi (2017)
A two-stroke poppet valve engine is developed to overcome the common problems in conventional two-stroke engine designs. However, replacing piston control port with poppet valve will resulted different flow behaviour. This paper is looking at experimental assessment on a two-stroke poppet valve engine configuration to investigate the port flow performance. The aims are to evaluate the intake and exhaust coefficient of discharge and assess the twostroke capability of the cylinder head. The results has shown comparable coefficient of discharge values as production engine for the intake while the exhaust has higher values which is favourable for the two-stroke cycle operation.